Influence of Technical Quality and Coronal Restoration on Periapical Health of Root Canal Treatment Performed by Malaysian Undergraduate Students - Norazlina Mohammad; Faizah Abdul Fatah; Azlan Jaafar; Siti Hajar Omar; Aimi Amalina Ahmad; Abdul Azim Asy Abdul Aziz; Aws Hashim Ali Al-Kadhim (Wolters Kluwer - Medknow, 2024)
Indexed by Scopus